Ethanol Extract of Fresh Peel of Balangkasua Fruit (Lepisanthes alata (Blume) Leenh) as an Alternative Reagent in the Identification of Trichuris trichiura Eggs - Nafila, Nafila; Arsyad, Muhammad; Kartika Sari, Putri (Rifa'Institute, 2025)
Introduction: Soil-Transmitted Helminths (STH) remain a major public health concern, particularly in areas with limited sanitation. Conventional staining using 2% eosin, although effective, poses drawbacks due to its non-biodegradability, toxicity, and flammability. Objective: This study aimed to evaluate the potential of ethanol extract from the fresh peel of Balangkasua fruit (Lepisanthes alata (Blume) Leenh) as a natural alternative reagent for the identification of Trichuris trichiura eggs. Method: A laboratory-based experimental design was conducted using fecal samples containing STH eggs. The fruit peel extract was prepared through maceration with ethanol and tested at concentrations of 20%, 40%, 60%, 80%, and 100%, while 2% eosin served as the positive control. Staining quality was assessed based on egg color contrast, shell clarity, internal morphology, shape and size clarity, and background staining. Result and Discussion: Results showed that the 100% extract yielded the highest score (13), categorized as good staining quality, while lower concentrations (20%–80%) were classified as moderate. The positive control consistently achieved superior results (score 19, very good). Statistical analysis using the Kruskal–Wallis test revealed significant differences among treatment groups (p < 0.05). Conclusion: These findings demonstrate that L. alata peel extract possesses potential as an eco-friendly alternative stain, although further optimization of extraction methods, pigment stabilization, and validation across various STH species are necessary before replacing synthetic eosin in routine diagnostics